La gestión urbanística mixta en ciudades centrales : un estudio sobre la intervención en vacíos urbanos - Etulain, Juan Carlos (2007)
The aim of the doctoral thesis project is the theoretical and empirical study of the contributions generated to the city-planning management by the mixed implementation (public-private) of urban interventions in central cities. Within the orientation hypotheses we could consider that in the middle of the decade of the 80s, new directions in the emerging urban policies of the neo-liberal economic model in force, added to the accumulated deficits, the new urban requirements and the change of scale of the city, put in crisis the forms whereupon traditionally the State planned and managed the cities and induced innovations in the scope of city-planning management, based on a more dynamic character of the public action which implies a task of promotion and management beyond the single administration and regulation of the territory, along with the accomplishment of interventions arranged with the private and civic sector. In order to go in depth with the investigation, the study centers the attention within a limited field, defined by the interventions that operate on urban voids. The relatively small production of this type of investigations in the recent period, and the necessity to take an answering position that provides the tools for the improvement and aggiornamiento of the city-planning management, make favourable to carry out the critical discussion of the experiences of mixed management that must be studied as research field.